The configuration of teaching in the teaching project of the Pedagogy course: a case study (Olhar de Professor, 2011)
This article reflects on how the concept of teaching proposed in the Brazilian National Curriculum Guidelines - DCNP 2006 - for the Pedagogy Course and supported especially by Anfope (National Association for the Education of the Professionals of Education) is set in the Teaching Project of the pedagogy course of a public Institution of Higher Education. The qualitative research, in the form of an instrumental case study (André, 2005) included document analysis and semi-structured interviews, as well as the constant review of the literature. The configuration of teaching as a national common ground implies the confluence of a set of principles that should guide the curriculum. It should include: the relation between theory/practice and the emphasis on research and knowledge production; solid theoretical formation and interdisciplinary; democratic management; social political and ethical commitment; collective and interdisciplinary work and the incorporation of the concept of continuing education. From the analysis of the data collected, it was concluded that the configuration of teaching in the Pedagogy Course researched is based on the above principles which led to: restructuring the curriculum and academic activities; resizing of contents; introduction of new teaching methods; engaging students in their future working context since the early years; interdisciplinary thought and action; unity theory-practice. However, it should be emphasized that much of the individual and collective work of teachers is responsible for the successful development of teaching as a common base -articulated to research and the management of the Pedagogy Course studied.
Keywords: National curriculum guidelines. Teaching project. Pedagogy course. teaching.